[Tibor Szentvéry 1]
skating, sailing-boat, children playing,, music lesson, winter scenes, Christmas, children in the straw, the old Héviz bath, pig-feast, family-film, Pecs train station family is waiting the father, bicycle ballet-examination, 1940 winter, sledging, skating, snowball, baby&parents, Balaton, 1942 scout-fest, open-air bath in Pécs, peach from buds to fruits, boys boxing, playing music